Physician survey regarding updated PCV13 vaccine recommendations for adults ≥65 years. Issue 9 (14th May 2021) - Hurley, Laura P.; O'Leary, Sean T.; Kobayashi, Miwako; Crane, Lori A.; Cataldi, Jessica; Brtnikova, Michaela; Beaty, Brenda L.; Gorman, Carol; Lindley, Megan C.; Kempe, Allison
Abstract: Background: In June 2019, the Advisory Committee on Immunization Practices recommended discontinuing the routine use of the pneumococcal conjugate vaccine (PCV13) among adults aged ≥65 years and instead recommended PCV13 be used based on shared clinical decision making (SCDM). Objectives: We wanted to assess among primary care physicians (1) knowledge and attitudes regarding the new SCDM PCV13 recommendation and (2) how the new recommendation will affect their likelihood of recommending PCV13 to adults aged ≥65 years. Design: This was done by mail and internet‐based survey, which was conducted October 2019 through January 2020. The study was carried out on a nationally representative sample of general internists (GIMs) and family physicians (FPs). Results: The response rate was 64% (617/968, GIM 57%, FP 71%). Only 41% of respondents were aware of the SCDM PCV13 recommendation in adults aged ≥65 years; 76% agreed (37% "Strongly, " 39% "Somewhat") that their patients aged ≥65 years will get confused by having a SCDM recommendation for PCV13 and a routine recommendation for the pneumococcal polysaccharide vaccine (PPSV23); 60% agreed (18% "Strongly, " 42% "Somewhat") that they were unsure of what points to emphasize when having a SCDM conversation with an adult aged ≥65 years about receiving PCV13. Just over 50% reported they would be less likely to recommend PCV13 for adults aged ≥65 years as a result of the new recommendation, but 42% reported that their recommendation for PCV13 would not change. Conclusions: Word of the new ACIP recommendation for PCV13 for adults aged ≥65 years needs to be further disseminated. Investigation into why some physicians do not plan to change their recommendations is warranted.